THE INFLUENCE OF FINANCIAL GOVERNANCE ON FINANCIAL PERFORMANCETHROUGH APPARATUS COMPETENCE: A STUDY AT BPKAD OF TTS REGENCY - Febra Novita Penna; Petrus Emanuel De Rozari; Anthon Simon Y. Kerihi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of financial governance, encompassing accountability, transparency, efficiency and effectiveness, and regulatory compliance, on local government financial performance, as well as to examine the moderating role of apparatus competence at the Regional Financial and Asset Management Agency (BPKAD) of Timor Tengah Selatan Regency, East Nusa Tenggara Province. This study employs a quantitative-explanatory approach using total sampling with 259 respondents from 66 Regional Government Organizations (OPD). Data were collected through online questionnaires and analyzed using Structural Equation ModelingPartial Least Square (SEM-PLS) with SmartPLS 4.0 software. The results indicate that apparatus competence, efficiency and effectiveness, and regulatory compliance have a positive and significant influence on local government financial performance. In contrast, accountability and transparency do not exhibit a significant influence on financial performance. Regarding the moderation effects, apparatus competence does not significantly moderate the influence of any financial governance variables on financial performance at BPKAD TTS Regency. These findings suggest that efficiency, effectiveness, and regulatory compliance are strategic factors in improving regional financial performance, while apparatus competence needs to be developed more systematically in order to function as an effective moderator in the relationship between financial governance and financial performance.